(untitled) (Academicia Globe: Inderscience Research, 2021)
Curriculum and instruction programme is one of the compulsory courses that must be offered and passed in the faculty of education. The curriculum programme is also offered as a masters programme and PhD programme in many Universities across the country. The curriculum programme is facing many implementation problems in the Nigerian higher institutions. inadequate funding, shortage of curriculum lecturers, inadequate teaching and learning materials of curriculum programme, inadequate infrastructural facilities, brain-drain, corruption, strike action and insecurity were identified as problems facing the implementation of curriculum programme in the Nigerian higher institutions. To address the problems, the following were recommended: increase in the funding of curriculum programme, employment of more curriculum lecturers, provision of more instructional materials of curriculum programme, provision of adequate infrastructural facilities, motivate all the lecturers in the higher institutions to prevent brain-drain, fight all forms of corruption practices in the higher institutions, implement all agreements reached with different unions groups in the higher institutions and provision of adequate security in all higher institutions.